EMG Signal Analysis Using Intrinsic Mode Functions to Discriminate Upper Limb Movements - Karuna, M.; Guntur, Sitaramanjaneya Reddy (The ... CSI International Symposium on Artificial Intelligence & Signal Processing (Online), 2020)
In this modern era analysis of sEMG (Surface Electromyography) signals plays a supreme task in the areas of human-machine interaction, diagnosing neuromuscular disorders, rehabilitation, and numerous relevant applications. EMG demonstrates the electrical activity during the contraction of the skeletal muscle. Purpose of this research is to distinguish the various muscle responses of the forearm with Empirical Mode Decomposition (EMD) and calculated Time-domain (TD) features of 10 intact subjects' benchmark EMG data base called Ninapro, in which database-2 has been used for identifying the basic wrist movements.